Paleolithic-Neolithic transition and late-to-postglacial climate change in East Asia: A review of archaeological data from karst caves in Southern China. (10th February 2022) - Gorodetskaya, Olga; Hsieh, Meng-Long; Guo, Li-Xin; Chiu, Pak-Hei
Abstract: We review the archaeological, chronological, and biological data from multiple karst caves in southern China that date to the late-Paleolithic to early-Neolithic transition. Our review shows that the radiocarbon dates, although having a large quantity, do not align with the known cultural sequences correlated among the cave sites (based on the degree of sophistication of artefact manufacturing) and they conflict with the corresponding paleoclimatic conditions revealed by the biological data. Most of these radiocarbon dates are older than expected, and their samples probably incorporate dead carbon through the reaction with groundwater. We argue that, when correlated with global paleoclimate records, the chronological framework provided by the biological datasets provides a more robust chronology than the available radiocarbon dates. Accordingly, all the Neolithic layers reviewed, with their plentiful biological remains of tropical/subtropical and aquatic/water-loving species, are likely to have been deposited in Holocene, and the Paleolithic cultural layers likely date to the Younger Dryas or the Bølling-Allerød. Our review suggests that the late-to-postglacial climate change helped initiate the development of Neolithic cultures in East Asia. We attribute this development to the growth of creeks/wetlands and their associated ecosystems (including the spreading of wild rice) during the period of climate warming and wetting, which greatly increased accessible food, water, and mud resources, providing opportunities for ancient peoples to recognize wild rice and to invent polishing stone tools and making pinched earthenware.